2019
DOI: 10.1016/j.tcr.2019.100222
|View full text |Cite
|
Sign up to set email alerts
|

Pure divergent dislocation of the index and middle finger carpometacarpal joints: A rare case

Abstract: A pure divergent dislocation involving the index and middle finger carpometacarpal joints is an extremely rare injury. We present a case of 21-year-old military man, victim of a motor vehicle accident, admitted at the emergency department unable to move his left hand with major swelling. X-rays and CT scan showed a dorsal dislocation of second and palmar dislocation of the third carpometacarpal joints without associated fracture, In the Operating room under general anesthesia, patient underwent closed reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(7 reference statements)
0
1
0
2
Order By: Relevance
“…The dislocation of the 2 nd and 3 rd CMC, volar or dorsal, has been reported in the literature. 14 Zaizi et al 15 published a case of divergent dislocation, in which the 3 rd CMC moved to volar, and the 2 nd CMC dislocated to the dorsal region. Mane et al 16 showed an undiagnosed lesion in a patient who had volar dislocation of the five carpometacarpal joints.…”
Section: Epidemiology and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The dislocation of the 2 nd and 3 rd CMC, volar or dorsal, has been reported in the literature. 14 Zaizi et al 15 published a case of divergent dislocation, in which the 3 rd CMC moved to volar, and the 2 nd CMC dislocated to the dorsal region. Mane et al 16 showed an undiagnosed lesion in a patient who had volar dislocation of the five carpometacarpal joints.…”
Section: Epidemiology and Classificationmentioning
confidence: 99%
“…A luxação do 2° e 3° MTC, volar ou dorsal, tem sido relatada na literatura. 14 Zaizi et al 15 publicaram um caso de luxação divergente, em que o 3° MTC deslocou-se para volar e o 2° MTC luxou para a região dorsal. Mane et al 16 mostraram uma lesão não diagnosticada numa paciente que teve luxação volar das cinco articulações CMCs.…”
Section: Epidemiologia E Classificaçãounclassified
“…A luxação do 2°e 3°MTC, volar ou dorsal, tem sido relatada na literatura. 14 Zaizi et al 15 publicaram um caso de luxação divergente, em que o 3°MTC deslocou-se para volar e o 2°M TC luxou para a região dorsal. Mane et al 16 mostraram uma lesão não diagnosticada numa paciente que teve luxação volar das cinco articulações CMCs.…”
Section: Anatomia E Cinesiologiaunclassified
“…Treatment is determined by the severity of the dislocation, stability of the CMC joints, and the time of hand injury management. Closed reduction is usually possible when the dislocation is recent, whereas open reduction is required for dislocations more than 15 days old [ 4 ].…”
Section: Introductionmentioning
confidence: 99%